The Potency of Aling Aling Sambangan Village as The Sport Tourism Icon In Buleleng, Bali - I Ketut Sudiana; I Ketut Yoda; Ketut Chandra Adinata Kusuma; Yovhandra Ockta (Postgraduate, University of Mataram, 2024)
The study objective to be achieved in this research is the formation of several tourism sports potentials that are worth selling in Sambangan village that are environmentally friendly without prejudice to local customary rules. This type of research is descriptive research. The methods that will be used to achieve the objectives of this research are observation, interviews and documentation methods. The data analysis will be carried out using a Qualitative SWOT Analysis model which is expected to also reveal possible alternative strategies for developing sports tourism in the Sambangan Tourism Village. The results obtained are as follows, several tourist sports that are worthy of being developed, such as trekking, jumping, swimming, climbing, and tubing. Constraints on the development of tourism sports are very limited to sports budgets and human resources. Management is handed over to each tourist attraction management group under Pokdarwis which is coordinated by BUMDES Sambangan village. So far there has been no maximum cooperation between village government and regional government. The people of Sambangan village hope that the regional government can publicize and promote the existence of tourist sports objects to relevant agencies both nationally and internationally so that tourist sports activities can run optimally and smoothly